Folate Receptor Alpha Upregulates Oct4, Sox2 and Klf4 and Downregulates miR‐138 and miR‐let‐7 in Cranial Neural Crest Cells. (28th June 2016) - Mohanty, Vineet; Shah, Amar; Allender, Elise; Siddiqui, M. Rizwan; Monick, Sarah; Ichi, Shunsuke; Mania‐Farnell, Barbara; G. McLone, David; Tomita, Tadanori; Mayanil, Chandra Shekhar
Abstract : Prenatal folic acid (FA) supplementation prevents neural tube defects. Folate receptor alpha (FRα) is critical for embryonic development, including neural crest (NC) development. Previously we showed that FRα translocates to the nucleus in response to FA, where it acts as a transcription factor. In this study, we examined if FA through interaction with FRα regulates stem cell characteristics of cranial neural crest cells (CNCCs)‐critical for normal development. We hypothesized that FRα upregulates coding genes and simultaneously downregulates non‐coding miRNA which targets coding genes in CNCCs. Quantitative RT‐PCR and chromatin immunoprecipitation showed that FRα upregulates Oct4, Sox2, and Klf4 by binding to their cis ‐regulator elements‐5′ enhancer/promoters defined by H3K27Ac and p300 occupancy. FA via FRα downregulates miRNAs, miR‐138 and miR‐let‐7, which target Oct4 and Trim71 (an Oct4 downstream effector), respectively. Co‐immunoprecipitation data suggests that FRα interacts with the Drosha‐DGCR8 complex to affect pre‐miRNA processing. Transfecting anti‐miR‐138 or anti‐miR‐let‐7 into non‐proliferating neural crest cells (NCCs) derived from Splotch ( Sp −/− ), restored their proliferation potential. In summary, these results suggest a novel pleiotropic role of FRα: (a) direct activation of Oct4, Sox2, and Klf4 genes; and (b) repression of biogenesis of miRNAs that target these genes or their effector molecules. Stem Cells 2016;34:2721–2732 Abstract : Hypothetical model of FRα function in NCCs. In response to FA, FRα translocates to the nucleus where it binds the cis ‐regulatory elements of Oct4, Sox2, and Klf4, activating transcription; this in turn activates downstream targets such as Trim71 and downregulates levels of miR‐138 and miR‐let‐7, which target Oct4 and Trim71 respectively thus removing the inhibitory effects on Oct4 and Trim71 expression.